1971
DOI: 10.1017/s0043174500049195
|View full text |Cite
|
Sign up to set email alerts
|

Picloram Persistence in Semiarid Rangeland Soils and Water

Abstract: Residues in soil, following application of 0.25 lb/A of 4-amino-3,5,6-trichloropicolinic acid (picloram) to semi-arid rangelands, usually were restricted to the top 12 inches for 60 days. Five ppb or less picloram were detected below 12 inches at 120 to 180 days after application; but picloram usually dissipated from the soil profile within a year. More picloram was detected 5 months after application at 6 to 18 inches deep at the lower ends of plots with 3% slopes than in plots with 0, 1, or 2% slopes. Runoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Possibly, the amount of rain in the fall of 1985 was insufficient to leach the picloram from the pea straw and soil surface to a depth where the herbi cide would be available for root uptake by the wheat. This explanation is supported by Scifres et al (14), who reported that only 22% of applied picloram was found below the top 2.5 cm of a sandy loam 28 d after treatment and after about 2.5 cm of rain. The concentra tion of picloram in the top 2.5 cm decreased 86% in 10 d in the absence of rain.…”
Section: Ogg and Young: Herbicide Toxicity To Winter Wheatmentioning
confidence: 57%
“…Possibly, the amount of rain in the fall of 1985 was insufficient to leach the picloram from the pea straw and soil surface to a depth where the herbi cide would be available for root uptake by the wheat. This explanation is supported by Scifres et al (14), who reported that only 22% of applied picloram was found below the top 2.5 cm of a sandy loam 28 d after treatment and after about 2.5 cm of rain. The concentra tion of picloram in the top 2.5 cm decreased 86% in 10 d in the absence of rain.…”
Section: Ogg and Young: Herbicide Toxicity To Winter Wheatmentioning
confidence: 57%
“…In addition, picloram may be an environmental hazard in some situations. Picloram may readily leach through a sandy soil profile and can move laterally with soil water (Keys and Friesen 1968;Scifres et al 1971). Picloram generally is applied with 2,4-D to reduce both the herbicide use rate and increase long-term control (Lym 1997).…”
Section: Introductionmentioning
confidence: 99%
“…_ of phenoxy herbicides and dicamba from aqueous systems. follows a concentration-dependent curve proceeding rapidly at Goring, C. A. I., J. D. Griffith, F. C. O'Melia, H. H. Scott, and C. R. first then slowing as picloram concentration in the water is sediment (Bailey et al 1970;Frank and Comes 1967);however, Weed Sci. 18:110-111. it is doubtful that picloram is highly adsorbed in view of…”
Section: Microbial Decomposition Is An Important Mode Of Dissipationmentioning
confidence: 99%